STAKEHOLDERS PERCEPTION OF INDO-ASEAN FREE TRADE AGREEMENT ON INDIAN FISHERIES SECTOR - Salim, Shyam S.; Geetha, R. (Journal of Indian Fisheries Association, 2011)
Exports augment the economy with an increase in international trade, acceleration in output and provide an engine for growth. Free trade agreement (FTA) with huge economies provides ample scope for the integration of trade. In this context, FTA with ASEAN is a big boost for various sectors of Indian economy. It is a major step in Indias â€œLook Eastâ€ policy in reducing its dependence on trade with U.S. and E.U and will strengthen its regional dynamics on trade. The ASEAN-India FTA will see tariff liberalization of over 90 percent of products traded between the two dynamic regions and would eliminate tariffs for about 4000 products (which included electronics, chemicals, machinery, textiles, agriculture and fisheries) out of which duties for 3200 products will be reduced by December 2013, with brought down to zero or near zero levels by December 2016. This agreement is supposedly believed to have a huge impact on Indian fisheries sector too. The different stake holders are to perceive differently to the agreements. There are apprehensions to the primary stakeholders the fishermen that the cheaper imports of local popular varieties such as sardines, mackerels, other lesser pelagic, cephalopods, crustaceans, demersal etc. Which overlaps with the fish landings will spell doom to fishing communities. On the other hand the consumers, processors and exporters will be at advantage due to the ready availability of the fish to suit their taste and preferences and the capacity utilization of the processing plants and reaping in on the export economies of the scale. In this context, a detailed study on the impact of the FTA on Indian fisheries is warranted. This paper critically reviewed and analysed the perceptions on the impact of ASEAN agreement on the different stakeholderâ€™s viz., fishermen, consumers, exporters, processors, market functionaries and the resources. The study involved sampling of stakeholders which included 240 consumer respondents, 50 exporters and processors and 30 markets functionaries in wholesale and retail markets in Cochin. The possible impact on the primary stakeholders (traditional fishers) was analyzed using a case study approach based on the possibility of oil sardine imports to India by ASEAN countries. The analysis on the perception of the stakeholders indicated that the exporters / processors, marketers favoured the agreement in terms of reaping the export economies of scale and timely and incessant availability of raw materials and processors for the high capacity utilization of processing plants and economies of scale. The marketers perceived the year round availability and increased quantum of sale consequent to the agreement. The consumers also approved the agreement on the year round availability and price stability and affordability in the domestic market. The price analysis on the comparison of the landing centre price and import price of sardine from ASEAN countries indicated that the interest of the primary stakeholders are not jeopardized as the domestic landing centre price is still competitive than the import price from ASEAN countriesKeywords: Free trade agreement, ASEAN, Perception, Market functionaries, Landing centre price, Stakeholders, Economies of scale.